From crawling to sprinting: Community translation goes mainstream - Kelly, Nataly; Ray, Rebecca; DePalma, Donald A. (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
The notion that “two heads are better than one” is hardly new when applied to translation. The entire corpus of Buddhist sutras was translated into Chinese collaboratively by foreign and Chinese monks over a thousand-year period which began in the 1st century A.D. (Chueung, 2006). However, the dominant model used today for translation in the commercial sector depends on a process that largely inhibits collaboration. This article presents some of the latest findings from research on the state of community translation, based on multiple market research studies carried out over a five-year period, including a comparative analysis of 100 community translation environments and interviews with stakeholders. The research reveals that, over the course of the last several years, translation industry participants have been moving away from the traditional process toward a more dynamic and collaborative model. As community-based models have grown in popularity, distinct types of environments have emerged as well.